2021
DOI: 10.1002/adhm.202102044
|View full text |Cite
|
Sign up to set email alerts
|

Co3O4 Nanowires Capable of Discharging Low Voltage Electricity Showing Potent Antibacterial Activity for Treatment of Bacterial Skin Infection

Abstract: Overuse of antibiotics has led to multidrug resistance in bacteria, posing a tremendous challenge to the healthcare system. There is an urgent need to explore unconventional strategies to overcome this issue. Herein, for the first time, we report a capacitive Co 3 O 4 nanowire (NW) electrode coated on flexible carbon cloth, which is capable of eliminating bacteria while discharging, for the treatment of skin infection. Benefiting from the unique NW-like morphology, the Co 3 O 4 NW electrode with increased acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…Additionally, to our knowledge, the antibacterial performance against E. coli is the best reported to date for electrical antibacterial (Figure 3f ). [ 25 , 29 , 39 , 40 , 41 , 42 , 43 ] More importantly, the MCO still maintains exceeding antibacterial stability even after 8 cycles of charging–discharging (Figure 3g ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, to our knowledge, the antibacterial performance against E. coli is the best reported to date for electrical antibacterial (Figure 3f ). [ 25 , 29 , 39 , 40 , 41 , 42 , 43 ] More importantly, the MCO still maintains exceeding antibacterial stability even after 8 cycles of charging–discharging (Figure 3g ).…”
Section: Resultsmentioning
confidence: 99%
“…[ 27 , 28 ] Recently, a Co 3 O 4 nanowire electrode after charging at 2 V for 30 min exhibited a good antibacterial rate against E. coli (≈93.8%, 1 log reduction) within 30 min treatment, showing the great potential of Co 3 O 4 as promising post‐charging candidate for bacterial infection therapy. [ 29 ] However, the critical issue for Co 3 O 4 is that its antibacterial efficacy is still low owing to its insufficient active sites and limited ROS yield. In this work, we remove these roadblocks by decorating Co 3 O 4 (CO) nanoneedles grown on the flexible carbon cloth with a thin MnOOH nanoparticles, which remarkably boost their post‐charging antibacterial activity ( Scheme 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, the application of non-antibiotic treatments in the field of antibacterial has attracted distinguished attention. Unlike the antibacterial mechanism of antibiotics, there are neither adjoint toxic and adverse effects nor obtained drug resistance by using the therapeutics. Due to the inherent deep penetration, noninvasiveness, and local site targeting properties, the near-infrared (NIR)-responsive photothermal therapy (PTT) offers a promising alternative for antibacterial wound dressing fabrication. Photothermal-active materials such as metallic compounds, carbon nanomaterials, and organic dye have been completely studied for biomedical treatments. However, their applied exploration is limited by the high cost, tedious synthesis, low biocompatibility, and low biodegradation.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, the application of non-antibiotic treatments in the field of antibacterial has attracted distinguished attention. 19 26 Unlike the antibacterial mechanism of antibiotics, there are neither adjoint toxic and adverse effects nor obtained drug resistance by using the therapeutics. Due to the inherent deep penetration, noninvasiveness, and local site targeting properties, the near-infrared (NIR)-responsive photothermal therapy (PTT) offers a promising alternative for antibacterial wound dressing fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…12,22,[26][27][28][29] It has been reported that nanomaterial surface modification based on charge (polarity and magnitude) shows a virucidal effect by disturbing the surface potential of viral particles and distorting the viral capsid via van der Waals and electrostatic interactions. 3,30,31 Applying an external low-voltage potential to different materials such as laser-induced graphene (LIG), 23,32,33 sulfur-doped LIG electrodes, 34 graphene-coated non-woven air filters, 35 Cu foam electrodes 36 and Co 3 O 4 nanowires 37 have been reported to kill bacteria and viruses. As an example, Ghatak, et al 1 have shown that a weak electric field (0.5 V) generated by an electroceutical fabric can disrupt the infectivity of coronavirus upon contact by destabilizing the electrokinetic properties of the virion.…”
Section: Introductionmentioning
confidence: 99%